Internet addiction and suicidal behavior among vocational high school students in Hunan Province, China: A moderated mediation model - Teng, Ziwei; Zhang, Yaru; Wei, Zirou; Liu, Mengdong; Tang, Meidai; Deng, Yizhi; Chen, Zhuohui; Wu, Ying; Liu, Runqi; Yang, Yuanguang; Gao, Menghui; Kun, Jin; et al. (Frontiers in Public Health, 2023)
Background: Vocational education is an important part of high school education in China. However, there is little research on high school students’ mental health. This study aimed to investigate the prevalence of suicidal behavior (SB) among this population and the mediating role of insomnia, depression, anxiety, and stress in the relationship between Internet addiction (IA) and SB using a structural equation model. Methods: A cross-sectional questionnaire survey was conducted among several vocational high school students in Hunan Province, and 7,968 valid questionnaires were obtained. General demographic data and data from the Dual-Mode Self-Control Scale, Athens Insomnia Scale, Depression Anxiety Stress scale-21, and Revised Chen Internet Addiction Scale were collected. A structural equation model was used to explore the different pathways from IA to SB. Results: Among the participants, 37.7%, 15.7%, and 21.8% reported suicidal ideation, plans, and attempts, respectively. The structural equation model confirmed that IA was indirectly related to SB and was mediated by insomnia and/or depression, anxiety, and stress. Limitations: First, we only recruited students from vocational schools in Hunan Province, therefore, the sample may not represent the entire population of vocational students in China. Second, self-report scales were used in this study, and clinical diagnosis required professional interviews. Third, since this study had a cross-sectional design, the causal relationship between the variables could not be determined. Conclusions: The prevalence of SB among vocational high school students in China was significantly high. The prevention of SB related to IA can be attributed to the improvement of insomnia and emotional problems.